Development and evaluation of a short-range applicator for treating superficial moving tumors with respiratory-gated spot-scanning proton therapy using real-time image guidance. (27th January 2016) - Matsuura, Taeko; Fujii, Yusuke; Takao, Seishin; Yamada, Takahiro; Matsuzaki, Yuka; Miyamoto, Naoki; Takayanagi, Taisuke; Fujitaka, Shinichiro; Shimizu, Shinichi; Shirato, Hiroki; Umegaki, Kikuo
Abstract: Treatment of superficial tumors that move with respiration (e.g. lung tumors) using spot-scanning proton therapy (SSPT) is a high-priority research area. The recently developed real-time image-gated proton beam therapy (RGPT) system has proven to be useful for treating moving tumors deep inside the liver. However, when treating superficial tumors, the proton's range is small and so is the sizes of range straggling, making the Bragg-peaks extremely sharp compared to those located in deep-seated tumors. The extreme sharpness of Bragg-peaks is not always beneficial because it necessitates a large number of energy layers to make a spread-out Bragg-peak, resulting in long treatment times, and is vulnerable to motion-induced dose deterioration. We have investigated a method to treat superficial moving tumors in the lung by the development of an applicator compatible with the RGPT system. A mini-ridge filter (MRF) was developed to broaden the pristine Bragg-peak and, accordingly, decrease the number of required energy layers to obtain homogeneous irradiation. The applicator position was designed so that the fiducial marker's trajectory can be monitored by fluoroscopy during proton beam-delivery. The treatment plans for three lung cancer patients were made using the applicator, and four-dimensional (4D) dose calculations for the RGPT were performed using patient respiratory motion data. The effect of the MRF on the dose distributions and treatment time was evaluated. With the MRF, the number of energy layers was decreased to less than half of that needed without it, whereas the target volume coverage values (D99%, D95%, D50%, D2%) changed by less than 1% of the prescribed dose. Almost no dose distortion was observed after the 4D dose calculation, whereas the treatment time decreased by 26%–37%. Therefore, we conclude that the developed applicator compatible with RGPT is useful to solve the issue in the treatment of superficial moving tumors with SSPT.